La economía sumergida en el Ecuador: tamaño, causas y consecuencias - Andrade , Nadia (2020)
Ecuadorian shadow economy is a core issue for firms, government and society in general. Its size, causes and consequences dircotly affcct the sectors previously cited. This work attempts to give an idea of what are the causes and consequences of the existence of an informal sector in the economy and, by using the most relevant methodologies, tries to estimate its size and its historical evolution. For this we use two methodologies: electricity usage methodology and currency demand methodology. Knowing the causes, size and consequences generated by the existence of an underground economy will allow policymakers to develop more consistent policies and to get better estimates of the feasible results of its applications.